Упростите выражения: 1. -3x(2-x)+(3x+1)(x-2) 2. 3(2x-1)^2+12x 3. (x+3)^2-(x-2)(x+2)

0 голосов
24 просмотров

Упростите выражения:
1. -3x(2-x)+(3x+1)(x-2)
2. 3(2x-1)^2+12x
3. (x+3)^2-(x-2)(x+2)


Алгебра (12 баллов) | 24 просмотров
Дан 1 ответ
0 голосов

Решите задачу:

1)-3x(2-x)+(3x+1)(x-2)=-6x+3 x^{2} +3 x^{2} -6x+x-2=\\=6 x^{2} -11x-2 \\ \\ 2)3(2x-1) ^{2} +12x=3(4 x^{2} +1+4x)+12x=12 x^{2} +3+12x+12x=\\=12 x^{2} +24x+3 \\ \\ 3)(x+3) ^{2} -(x-2)(x+2)= x^{2} +9+6x-( x^{2} -4)= \\ = x^{2} +9+6x- x^{2} +4=6x+13
(40.4k баллов)